2008
DOI: 10.1007/s11605-008-0598-4
|View full text |Cite
|
Sign up to set email alerts
|

Enteral Stents for Malignancy: A Report of 46 Consecutive Cases over 10 years, with Critical Review of Complications

Abstract: SEMS effectively palliate gastric outlet obstructions that result from upper gastrointestinal malignancies. Their benefits offset potential complications or malfunctions, when a pluridisciplinary approach is adopted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 14 publications
3
28
0
1
Order By: Relevance
“…Looking at the long term results and complications of enteral stent placement for unresectable cancer, Phillips et al [21] reviewed the outcomes of 46 patients with malignant gastric outlet obstruction. All patients had successful stent placement and 42 patients (91%) showed clinical improvement.…”
Section: Complicationsmentioning
confidence: 99%
“…Looking at the long term results and complications of enteral stent placement for unresectable cancer, Phillips et al [21] reviewed the outcomes of 46 patients with malignant gastric outlet obstruction. All patients had successful stent placement and 42 patients (91%) showed clinical improvement.…”
Section: Complicationsmentioning
confidence: 99%
“…37,38 However, SEMS can become obstructed or overgrown by tumor resulting in reduced luminal patency (57% in one study) after 6 months. 39 With the recent development of LAMS, Tyberg et al 40 examined the utility of LAMS for EUS-guided GJ (EUS-GJ) in patients with benign and malignant GOO. In an international, prospective trial of 26 patients with GOO, the authors demonstrated technical success of EUS-GJ using LAMS in 24 patients (92.3%).…”
Section: Other Procedures: Gastrojejunostomy Eus-directed Transgastrmentioning
confidence: 99%
“…Massive bleeding related to an aorto-enteric fistula has been reported in one case that was managed with placement of a stent-graft in the aorta. 42 …”
Section: Major Complications Bleedingmentioning
confidence: 99%